Pengaruh Pendidikan Agama Islam Di Sekolah Terhadap Perilaku Anak Di Rumah - Muhammad Nasruddin; Endang Sriwinarsih; Yayah Rukhiyah; Supriyanti Supriyanti; Nginayatul Khasanah (UIN Sultan Maulana Hasanuddin Banten, 2021)
PAI at all levels of education aims to increase students' faith, understanding, appreciation and practice of the religion of Islam so that they become Muslim human beings who believe in Allah SWT, and have noble character in personal, social, national and state life. However, there are specific objectives that must be considered so that the influence of Islamic Education at the PAUD level can affect life outside of school and in the family. This quantitative research describes its influence, especially on the students of TK Aisyiyah 5, Magelang City, who identify its significance. For this reason, it is suggested to strengthen the reciprocal relationship between kindergarten and parents in addition to consistency in assisting children in learning Islamic Education at home. Keyword: effect, Islamic education, kindergatens students, familyReferencesAl-Amin, M. N. K. (2013). Keluarga Sebagai Dasar Pendidikan Agama Bagi Anak. INSANIA: Jurnal Pemikiran Alternatif Kependidikan, 18(1), 49–62. Arifin, M. (1977). Hubungan Timbal Balik Pendidikan Agama di Lingkungan Sekolah dan Keluarga sebagai pola pengembangan metodologi. Bulan Bintang. Arikunto, S. (2013). Prosedur Penelitian : Suatu Pendekatan Praktik (Edisi Revisi). Rineka Cipta. Azwar, S. (2017). Metode Penelitian. Pustaka Pelajar. Fathurohman, O. (2017). Hakikat Bermain Dan Permainan Anak Usia Dini Di Pendidikan Anak Usia Dini (PAUD). As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 2(1), 27–36. Hasbullah, H. (2018). Karekteristik Pendidikan Islam Menurut Imam Al-Ghazali Proses Pendidikan Islam Yang Berkelanjutan Dan Berangsur-Angsur. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 2(2), 85–93. Hisyam, M. R., Suyanto, Sadzili, M., Arifin, Z., & Rahman, A. S. (2019). Peran Anggota Keluarga Berketahanan Dalam Perspektif Quran. Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 9(2), 171–186. Huliyah, M. (2016). Hakikat Pendidikan Anak Usia Dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 60–71. Hurlock, E. B. (2016). Perkembangan Anak (Vol. 2). Penerbit Erlangga. Imroatun, I. (2017). Pembelajaran Huruf Hijaiyah bagi Anak Usia Dini. Proceedings of The 2nd Annual Conference on Islamic Early Childhood Education, 175–188. Imroatun, I., Nirmala, I., Juhri, J., & Muqdamien, B. (2020). Kajian Literatur Pengasuhan Anak Usia Dini Dalam Islam. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(1), 57–66. Kartono, K. (2006). Psikologi Anak, Psikologi Perkembangan. Mandar Maju. Kurniawan, H. (2018). Pengembangan Lingkungan Belajar Literasi Untuk Anak Usia Dini. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 2(1), 45–56. Ma’shumah, L. A. (2001). Pembinaan Kesadaran Beragama pada Anak : Telaah PP No.27/1990 dalam Konteks Pendidikan Islam. In S. Ismail & N. Huda (Ed.), Paradigma Pendidikan Islam. Putra Pelajar. Majelis Pendidikan Dasar dan Menengah Pimpinan Cabang Aisyiah. (2003). Kurikulum TK Aisyiyah. Majelis Pendidikan Dasar dan Menengah Pimpinan Cabang Aisyiah. Mualimin, M. (2017). Konsep Fitrah Manusia Dan Implikasinya Dalam Pendidikan Islam. Al-Tadzkiyyah: Jurnal Pendidikan Islam, 8(2), 249. https://doi.org/10.24042/atjpi.v8i2.2130Muhaimin. (2004). Wacana Pengembangan Pendidikan Islam. PSAPM dan Pustaka Pelajar. Nadjih, D., & Imroatun, I. (2016). Hadits Tentang Pendidikan Jasmani Anak Usia Dini. Prosiding Seminar Nasional Peran Pengasuhan Anak Raudhatul Atfal Dalam Membangun Karakter Bangsa, 51–64. Nugraha, E. (2020). Implementasi Program Tahfizh Qur’an Di PAUD Inklusif Dengan Model HOTS. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(2), 95–106. Rahayu, S. H., Haroen, H., Budiutomo, T., Khasanah, N., & Nuryati. (2020). Manajemen Mutu Layanan Ta’lim Quran lil Aulad (TQA) di Yayasan Team Tadarus “AMM” Yogyakarta. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 5(2), 117–130. Rahman, H. S. (2002). Konsep Dasar Pendidikan Anak Usia Dini. PGTKI Press. Santhut, K. A. (1998). Menumbuhkan Sikap Sosial, Moral dan Spiritual Anak Salam Keluarga Muslim (I. Burdah (penerj.)). Mitra Pustaka. Sudjiono, A. (2010). Pengantar Statistik Pendidikan. PT Rajagrafindo. Sugiyono. (2016). Metode Penelitian Kuantitatif, Kualitatif, Dan RnD. ALFABETA. Syaodih, N. (2006). Metode Penelitian Pendidikan,. Remaja Rodakarya. Thoha, M. C., NC, F. S., & Priyono. (1996). Epistemologi dalam Pendidikan Islam dalam Reformulasi Pendidikan Islam, (Yogyakarta: Pustaka Pelajar, 1996). Pustaka Pelajar. Tsani, I. (2013). PENDIDIKAN AGAMA ISLAM SEBAGAI SARANA PEMBENTUKAN MORAL DAN KARAKTER SISWA. Didaktika Religia, 1(1). https://doi.org/10.30762/didaktika.v1i1.112Uyuni, Y. R. (2019). Konsep Pola Asuh Orang Tua Dalam Perspektif Islam Terhadap Tumbuh Kembang Anak Dalam Keluarga. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 4(1), 53–64. Zuhairini dkk. (2009). Filsafat Pendidikan Islam. Bumi Aksara.